2021
DOI: 10.52922/ti78207
|View full text |Cite
|
Sign up to set email alerts
|

Responding to cybercrime: results of a comparison between community members and police personnel

Abstract: Advancements in information technology are sources of both opportunity and vulnerability for citizens. Previous research indicates that there are significant challenges for police in investigating cybercrime, that community expectations about police responses are based largely on media representations, and that victims experience high levels of frustration and stigmatisation. This paper examines the views of the Australian community and law enforcement officers about the policing of cybercrime. Results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Australian officers and analysts identified a brain-drain of qualified staff moving to the private sector, suggesting how to attract and keep talent lay in providing additional professional development education, given the short shelf life of effective techniques and the rapidly evolving nature of offending (Harkin et al , 2018). A study of police, cybersecurity experts and civilian perspectives on digital crime in Australia revealed that the readiness of law enforcement to address and investigate digital criminal activity was related to their level of exposure to previous cybercrime cases as well as their knowledge or awareness of the types of digital activity (Cross and Holt, 2021). Limited resources and concern over increasing moral panic or cyber hysteria were offered to explain reluctance among surveyed Canadian officers to engage with youth perpetrators of digital harms such as cyberbullying (Broll and Huey, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Australian officers and analysts identified a brain-drain of qualified staff moving to the private sector, suggesting how to attract and keep talent lay in providing additional professional development education, given the short shelf life of effective techniques and the rapidly evolving nature of offending (Harkin et al , 2018). A study of police, cybersecurity experts and civilian perspectives on digital crime in Australia revealed that the readiness of law enforcement to address and investigate digital criminal activity was related to their level of exposure to previous cybercrime cases as well as their knowledge or awareness of the types of digital activity (Cross and Holt, 2021). Limited resources and concern over increasing moral panic or cyber hysteria were offered to explain reluctance among surveyed Canadian officers to engage with youth perpetrators of digital harms such as cyberbullying (Broll and Huey, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, although victim blame has been established as a consistent experience for online fraud victims, there is little research on why this may be the case. The dominant perspective in the sparse extant literature on victim blame in online fraud adopts Nils Christie's (1986) "ideal victim" thesis (Mazurek, 2019;Sorell and Whitty, 2019;Cross et al, 2019;Cross et al, 2021;Notte et al, 2021). Christie (1986) argued that to be considered a "real" victimand thus deserving of unequivocal victim statusan individual must be weak (sick, old or very young); be carrying out a "respectable project" at the time of victimisation; and be victimised at a place they cannot be blamed for being in.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars agree that the blame experienced by victims of online fraud [and related offences such as art fraud (Nelson and Nelson, 2013;Mazurek, 2019)] can likewise be understood through Christie's (1986) lens (Nelson and Nelson, 2013;Mazurek, 2019;Cross et al, 2019;Sorell and Whitty, 2019;Notte et al, 2021;Cross et al, 2021). According to these scholars, victims of online fraud are not, as a group, deemed especially weak or vulnerable, and cannot be considered to be carrying out a respectable project (because they are often attempting to "get rich quick" for example) or to be in an environment (the internet) that they cannot be blamed for being in.…”
Section: Introductionmentioning
confidence: 99%